Risk factors and the occurrence of cerebral palsy in high risk infants - Setyo Handryastuti; Sofyan Ismael; Sudigdo Sastroasmoro; Asril Aminulah; Ferial Hadipoetro Idris; Adji Saptogino; Sunartini Hapsara (Indonesian Pediatric Society, 2018)
Background The incidence of cerebral palsy (CP) has increased due to better survival rates of high-risk babies. Early detection and time to the occurrence of CP in the first year of life is important in order to provide early intervention.Objectives To determine the proportion of CP in high-risk babies, the time to the occurrence of CP in the first year, and assess possible associations between risk factors of CP and time to the occurrence of CP.Methods A prospective cohort study was done on 150 high-risk babies up to the age of 12 months. We obtained history of motor ability and assessed primitive reflexes and postural reactions of subjects at the ages of 4 and 6 months. The diagnosis of CP was established at 6 and 12 months of age.Results The proportion of CP was 26% at 6 months and 24% at 12 months of age. Significant risk factors associated with CP at 6 and 12 months of age were cerebral ultrasound abnormalities, hypoxic-ischemic encephalopathy, and intracranial hemorrhage. In 88.7% of subjects with CP, CP was detected in the first 6 months. Mean age at the occurrence of CP was 9.99 months (95%CI 9.46 to 10.53). Risk factors that significantly affected the time to the occurrence of CP by survival analysis were ultrasound abnormalities and hypoxic-ischemic encephalopathy.Conclusions Cerebral palsy can be detected as early as the first 6 months of life. Cerebral ultrasound abnormalities and hypoxic ischemic encephalopathy are the risk factors associated with CP.